Study on the Path of Low-Carbon Development of Huaihe River Ecological Economic Belt under Dual-Carbon Goal - Pu, Mengmeng; Zhang, Hanning; Duan, Lingjing; Li, Jihui (International Journal of Global Economics and Management, 2024)
The twentieth CPC National Congress proposed accelerating the transition to green development of society; green water and green mountains are golden silver mountains, and the realization of regional green development is an important connotation of high-quality economic development. The Huaihe River Ecological and Economic Belt is an important ecological barrier and economic zone in China, and it is of great significance for China's green and low-carbon development to promote the realization of the “dual-carbon” goal in the region. In recent years, the Huaihe River Ecological Economic Zone has achieved certain results in promoting regional green and low-carbon development, but the measurement of green and low-carbon development data in different regions reveals that the resource endowment and development level of different regions have large differences. This paper adopts the research method of establishing an indicator system to measure and assess the development level of green low-carbon construction in various regions of the Huaihe River Ecological Economic Belt, and combines with case studies to propose optimization paths from the perspectives of constructing green and economical infrastructures, attaching importance to a humane public environment, and implementing green innovations, so as to help the development of green low-carbon construction in the region.